Political Economy Analysis (Pea) And Market Analysis Of Illicit Wildlife Trafficking (A Case Study On Pangolin Illicit Trafficking: Indonesia-China) - Bintang Cahya Sakti (Jurnal Ilmu Kepolisian, 2022)
This paper aims to formulate and examine the best intervention model in countering pangolin trafficking. This involves the political economy analysis (PEA) and the market analysis, prioritising through harm identification, and the response by intervention formulation. The preferred intervention is then examined by the theory of change to determine its process in pursuing the impact. It utilises qualitative approach by using document reviews as data collection method. This paper finds that pangolin market is led by the “push” factors in Indonesia influenced by the geographical condition, which has a wide range of tropical forests as pangolin habitat. Moreover, the low level of GDP and education rates is the main factor behind pangolin trading. While, the “pull” factors in China are influenced by the high demand rates that cannot be covered by its local pangolins population. Finally, the author suggests that the general deterrence approach is regarded as the best model to intervene in the market. This approach could reduce the supply and demand to cut the market chain.Keywords: political economy analysis, market analysis, general deterrence, wildlife trafficking, pangolin.